Age-dependent regional changes in the rostral migratory stream - Mobley, Arie (2013)
Throughout life the subventricular zone (SVZ) is a source of new olfactory bulb (OB) interneurons. From the SVZ, neuroblasts migrate tangentially through the rostral migratory stream (RMS), a restricted route ~5 mm long in mice, reaching the OB within 10-14 days. Within the OB neuroblasts migrate radially to the granule and glomerular layers where they differentiate into granule and periglomerular (PG) cells and integrate into existing synaptic circuits. SVZ neurogenesis decreases with age, and may be a factor in age-related olfactory deficits. However, the effect of aging on the RMS and on the differentiation of interneuron subpopulations remains poorly understood. Here, we examine RMS cytoarchitecture, neuroblast proliferation and clearance from the RMS, and PG cell subpopulations in 6, 12, 18 and 23 months of age. We find that aging affects the area occupied by newly generated cells within the RMS and regional proliferation, while the clearance of neuroblasts from the RMS and PG cell subpopulations and distribution remain stable.